Empowering Learners: Challenges in Promoting Self-Regulated Learning in Indonesian Senior High School EFL Classroom - Dhiasa, Indah Swandewi; Nugroho, Him’mawan Adi; Widyastuti, Widyastuti (Jetlal, 2025)
The Minister of Education of the Republic of Indonesia introduced the Merdeka Curriculum in 2022, which emphasizes fostering self-regulated learners by adopting a student-centered approach tailored to their interests and needs. Self-regulated learning (SRL) is established as a core competency standard across educational levels, from primary to high school. Despite its significance, EFL teachers face challenges in promoting SRL in the classroom. This study aimed to identify these challenges using a multiple-case study method, which is well-suited for examining complex issues in real-world contexts. The findings revealed notable differences in students' self-regulation capabilities within the same classroom, making it difficult for teachers to manage groups with varying levels of SRL. Additionally, the lack of continuous training and professional development further hinders teachers’ ability to support SRL effectively. Another challenge identified was the prioritization of subject matter instruction over SRL due to the curriculum’s rigid content and pedagogical framework. These findings highlight the need for more flexible curriculum designs and enhanced teacher training programs to address the challenges of implementing SRL in EFL classrooms